Natural Products in the Treatment of Pulmonary Emphysema: Therapeutic Effects and Mechanisms of Action - Echeverria-Morgado, J (Elsevier GmbH, 2022)
Background: Chronic obstructive pulmonary disease (COPD) is a class of lung diseases including chronic bronchitis, asthma, and emphysema. Long-time smoking is considered the main reason for developing emphysema. Emphysema can be defined as damage to the walls of the air sacs (alveoli) of the lung. It has been demonstrated that natural compounds with antioxidant and anti-inflammatory effects can effectively improve or protect the lung against this disease. This paper is dedicated to systematically review the effective natural compounds in the treatment of pulmonary emphysema. Purpose: This is the first systematic and comprehensive review on the role of plant-derived secondary metabolites in managing and/or treating pulmonary emphysema Study design and Methods: A systematic and comprehensive review was done based on Scopus, PubMed, and Cochrane Library databases were searched using the "emphysema", "plant", "herb", and "phytochemical" keywords. Non-English, review, and repetitive articles were excluded from the study. Search results were included in the Prisma diagram. Results: From a total of 1285 results, finally, 22 articles were included in the present study. The results show that some herbs such as Scutellaria baicalensis Georgi and Monascus adlay and some phytochemicals such as gallic acid and quercetin and blackboard tree indole alkaloids affect more factors in improving the lung emphysema. Also, some natural compounds such as marijuana smoke and humic acid also play an aggravating role in this disease. It also seems that some of the medicinal plants such as PM014 herbal formula, pomegranate juice and açaí berry sometimes have side effects that are inconsistent with their therapeutic effects. Conclusion: We concluded that natural compounds can effectively improve pulmonary emphysema due to their antioxidant, anti-inflammatory, and anti-apoptotic properties. However, additional studies are suggested to prove efficacy and side effects. © 2022 Elsevier GmbH